Neonatal Intensive Care Unit Evacuation and Care During a Natural Disaster: The Experience of Cyclone Idai in Beira, Mozambique - Calgaro, Serena; Borellini, Martina; Seni, Amir Hussein Abubacar; Tirzi, Maria Concetta; Gimo, Antonio Marcos Dias; Cebola, Bonifacio Rodriguez; Putoto, Giovanni; Trevisanuto, Daniele (Frontiers in Pediatrics, 2020)
Global warming has increased the frequency of natural disasters, such as cyclones. Mozambique is considered one of the most vulnerable countries to extreme weather events. Natural disasters particularly affect vulnerable people, including preterm and critical ill infants of Neonatal Intensive Care Units (NICUs). Literature on NICU evacuations in the case of a natural disaster has been reported in high-resource settings, but it is lacking in low-resource settings. On the 14th of March 2019, a tropical cyclone (Idai) hit Mozambique. This report is a descriptive analysis of the experience of the NICU evacuation and care during and after cyclone Idai at Beira Central Hospital, Beira, Mozambique.